Spatial variations in trace element concentrations of the sea urchin, Paracentrotus lividus, a first reference study in the Mediterranean Sea. Issue 1 (April 2018) - Ternengo, S.; Marengo, M.; El Idrissi, O.; Yepka, J.; Pasqualini, V.; Gobert, S.
Abstract: A study on Trace Elements (TE) from sea urchin gonads has been conducted in the western Mediterranean Sea. Contamination data were used to determine a Trace Method Pollution Index (TEPI). TE concentrations varied considerably depending on the location of the sampling stations. The results showed that five trace elements (Zn, Fe, As, Al, Cu) are ubiquitous. The geographical area considered (Corsica) represents an important range of environmental conditions and types of pressure that can be found in the western Mediterranean Sea. TEPI was used to classify the studied sites according to their degree of contamination and allowed reliable comparison of TE contamination between local and international sites. TE contamination of the western Mediterranean Sea displayed a north-to-south gradient, from the Italian coasts down through the insular Corsican coasts to the north African littoral. Due to the increasing environmental pressure on the Mediterranean Sea, a regular monitoring of TE levels in marine organisms is necessary to prevent any further environmental deterioration. Highlights: Trace Elements varied depending on the location of the sampling stations. Five trace elements (Zn, Fe, As, Al, Cu) are ubiquitous. Trace Elements in the western Mediterranean Sea displayed a north-to-south gradient.